2021
DOI: 10.1039/d1sm00074h
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial-like aerogels for broadband vibration mitigation

Abstract: We report a mechanical metamaterial-like behavior as a function of micro/nanostructure of otherwise chemically identical aliphatic polyurea aerogels. Transmissibility varies dramatically with frequency in these aerogels. Broadband vibration mitigation is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…The most well-studied class of aerogels is based on silica. ,, However, silica aerogels are notorious for their fragility, which limits the range of their applications. One way to address the fragility issue of oxide aerogels is to apply a conformal nanothin polymer coating over their entire skeletal framework. These materials are referred to as X-aerogels, and their strength-to-mass ratio renders them suitable even for ballistic protection (armor). The topology of the nanoscopic composition of X-aerogels directed the rational design and development of purely polymeric aerogels from all major classes of polymers ranging from polyolefins, and phenolic resins including polybenzoxazines, polyimides, polyamides, and polyureas to polyurethanes. The latter class of aerogels includes recently reported rubber-like superelastic poly­(isocyanurate–urethane) (PIR–PUR) aerogels that show a strong nanostructure-dependent shape-memory effect triggered by a temperature swing around their glass transition temperature. …”
Section: Introductionmentioning
confidence: 99%
“…The most well-studied class of aerogels is based on silica. ,, However, silica aerogels are notorious for their fragility, which limits the range of their applications. One way to address the fragility issue of oxide aerogels is to apply a conformal nanothin polymer coating over their entire skeletal framework. These materials are referred to as X-aerogels, and their strength-to-mass ratio renders them suitable even for ballistic protection (armor). The topology of the nanoscopic composition of X-aerogels directed the rational design and development of purely polymeric aerogels from all major classes of polymers ranging from polyolefins, and phenolic resins including polybenzoxazines, polyimides, polyamides, and polyureas to polyurethanes. The latter class of aerogels includes recently reported rubber-like superelastic poly­(isocyanurate–urethane) (PIR–PUR) aerogels that show a strong nanostructure-dependent shape-memory effect triggered by a temperature swing around their glass transition temperature. …”
Section: Introductionmentioning
confidence: 99%
“…Owing to the unique combination of excellent properties such as low thermal conductivity, low dielectric constant, and a high-degree of flexibility, polymer aerogels have been considered a novel advanced material with high commercialization potential and therefore recently attracted research attention for vibro-acoustic mitigation applications. [32] Yao et al reported the first acoustic characterization of a phenolic aerogel material system that was prepared by freeze-drying method. [100] They studied a sandwich microstructural material system comprised of three layers whereby the top and bottom layers exhibited a pyknotic structure, and the middle layer exhibited irregularly dispersed nanopores.…”
Section: Acoustic Properties Of Polymer Aerogelsmentioning
confidence: 99%
“…The examples of aerogels with net-like morphology are shown in Figure 3, all for aerogels based on polymers: polyimide, cellulose (dissolved in 8%NaOH-water and gelled), pectin (cross-linked with calcium), and nanofibrillated cellulose. Depending on the synthesis conditions, the fibrils in some synthetic polymer aerogels (polyimide, polyurea) may have a "caterpillar" morphology (not shown, see, for example, [32,33] ).…”
Section: (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, polymer aerogels can be synthesized with a highly tortuous and mesoporous microstructure with excellent mechanical properties at a bulk density similar to the ones corresponding to silica aerogels [15][16][17][18][19][20] . Polymer aerogels exhibit high ductility with mechanical properties such as Young's modulus orders of magnitude higher than the corresponding values for silica aerogels [21][22][23][24] .…”
mentioning
confidence: 99%